2021
DOI: 10.1007/s00464-021-08593-w
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cholecystectomy following endoscopic retrograde cholangio-pancreatography is not associated with worse surgical outcomes

Abstract: Background There is no universal consensus on the optimal timing of cholecystectomy following endoscopic retrograde cholangio-pancreatography (ERCP). This study aims to evaluate the effect of time delay and post-ERCP complications on cholecystectomy outcomes. Materials and methods All patients who underwent pre-op ERCP for concurrent cholelithiasis and choledocholithiasis between January 2009 and August 2019 at University Hospitals Plymouth, UK, were included. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In addition, reviews showed that RBE is definitively lower if cholecystectomy is carried out early vs delayed (2–10% vs 24–47%) [ 13 , 15 , 29 31 ]. While a better reduction in the risk of RBE is achieved the sooner cholecystectomy is carried out [ 12 , 42 , 52 ], the definition of “early” cholecystectomy after endoscopic treatment of choledocholithiasis remains variable [ 1 , 28 , 53 ]. This is reflected in guidelines recommending early cholecystectomy after periods varying from 24 h to 4 weeks [ 2 , 5 7 , 12 , 18 , 20 , 22 , 32 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, reviews showed that RBE is definitively lower if cholecystectomy is carried out early vs delayed (2–10% vs 24–47%) [ 13 , 15 , 29 31 ]. While a better reduction in the risk of RBE is achieved the sooner cholecystectomy is carried out [ 12 , 42 , 52 ], the definition of “early” cholecystectomy after endoscopic treatment of choledocholithiasis remains variable [ 1 , 28 , 53 ]. This is reflected in guidelines recommending early cholecystectomy after periods varying from 24 h to 4 weeks [ 2 , 5 7 , 12 , 18 , 20 , 22 , 32 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Operative time may represent a surrogate of the difficulty of operation [ 53 ]. Operative time is higher after a previous ERCP [ 55 ], in emergency setting [ 28 ] and increases according to the number of episodes of cholecystitis [ 57 ]. Although the goal of this study was not to evaluate the relationship between cholecystitis and ERCP, its high incidence deserves to be considered as a contributing risk in the difficulty of delayed operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that delayed LC results in more morbidity and recurrent biliary symptoms ( 12 ). On the other hand, early LC can reduce re-admissions with gallstone-related symptoms and is not associated with worse surgical outcomes ( 8 ). Hence, early LC after ERCP in the same admission was adopted in our center.…”
Section: Introductionmentioning
confidence: 99%
“…However, the suitable interval time from ERCP to LC is still controversial and varies from hours to more than 6 weeks (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). It has been reported that delayed LC results in more morbidity and recurrent biliary symptoms (12).…”
Section: Introductionmentioning
confidence: 99%